Peranan UU Minerba sebagai Controls Host State Indonesia terhadap Kedudukan Kontrak Karya PT. Freeport Indonesia (PTFI) dan Negosiasi Menjadi Jalan Keluar - Sri Sinduwati (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2024)
Investment and implementation of mineral and coal mining business activities are regulated by the obligation to nationalize or divest shares in Article 112 of Law Number 3 of 2020 concerning Amendments to Law Number 4 of 2009 concerning Mineral and Coal Mining (UU 3 of 2020). This research aims to analyze the role of the Minerba Law as Indonesia's Controls Host State towards PT. Freeport Indonesia and the position of the Contract of Work. The research method in this paper uses normative-empirical legal research methods. The results of this research are that the provisions of Article 1123 of the Mining and Coal Law regulate that mining business entities whose shares are owned by foreigners are obliged to divest 51% (fifty one) percent of their shares in stages to the central government, regional government, BUMN, regionally owned business entities, and/ or national private business entities. The government's agreement with PT. Freeport Indonesia is related to the divestment of 51% (fifty one percent) shares as one of the strategic schemes that can be implemented under the coordination of the Ministry of BUMN in the acquisition process, namely through the formation of a BUMN Mining holding company where PT. Indonesia Asahan Aluminum (Inalum) will be the holding company.